Analisis Likuiditas Dan Profitabilitas Dalam Mengukur Kinerja Keuangan Perusahaan Yang Bergerak Pada Distribusi Batu Barapada Periode Tahun 2018-2022 : (study Kasus Pada PT.Batulicin Nusantara Maritim) - Mahandika Candra Kirana; Nur Ainiyah; Nurdiana Fitri Isnaini; Hartono Hartono (Jurnal Kendali Akuntansi, 2023)
The purpose of this research is to evaluate PT. Batulicin Nusantara Maritim's financial performance between 2018 and 2022 based on its profitability and liquidity ratios. The financial accounts of PT. Batulicin Nusantara Maritim, a coal transportation service provider listed on the investment gallery of the Indonesian Stock Exchange (GIBEI), are the subject of this study. An analysis of the documentation was the method employed to prepare this research. Data is collected through the study, recording, and classification of documentation. This study requires the gathering of data from a corporation in the form of financial reports, which will then be used as research material. The data was then compiled, classified, confidentially handled, and evaluated using quantitative descriptive analysis to offer a summary of the issues encountered or looked into. Results of the study The financial performance of PT. Batulicin Maritime Archipelago is impacted by the profitability ratio and liquidity ratio of PT. Batulicin Nusantara Maritim during the years 2018 to 2022. has an effect on the financial performance of PT. Batulicin Nusantara Maritim.